2022
DOI: 10.1021/acscatal.2c00087
|View full text |Cite
|
Sign up to set email alerts
|

Selective Enhancement of Methane Formation in Electrochemical CO2 Reduction Enabled by a Raman-Inactive Oxygen-Containing Species on Cu

Abstract: The role of oxygen-containing species on Cu catalysts in the electrochemical CO2 reduction reaction (CO2RR) remains unclear due to the difficulty in its stabilization under reaction conditions. Co-electrolysis of CO2 with an oxidant is an effective strategy to introduce oxygen-containing species on Cu during the CO2RR. In this work, we present concrete evidence demonstrating that an oxygen-containing species is able to not only enhance the rate of the CO2RR but also tune selectivities for certain products. Co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 113 publications
1
12
0
Order By: Relevance
“…This method improves our understanding of the electrocatalytic mechanism. 122 3.1.1. In Situ Surface Investigations.…”
Section: Investigating Adsorption Phenomenonmentioning
confidence: 99%
“…This method improves our understanding of the electrocatalytic mechanism. 122 3.1.1. In Situ Surface Investigations.…”
Section: Investigating Adsorption Phenomenonmentioning
confidence: 99%
“…In addition, oxygencontaining species are also present in the Raman spectra of Cu needle-Ag (dotted green lines at ≈320, ≈392, and ≈620 cm −1 ; these species do not have a direct correlation with CO 2 RR activity. [59,60] Figure S27 (Supporting Information) shows in situ Raman spectra of Cu particles and Cu needle. No prominent peaks of reaction intermediates were observed in their spectra, indicating that their CC coupling ability is relatively weak.…”
Section: Investigation Of Structural Effectsmentioning
confidence: 99%
“…Cu Oxide and Cu Hydroxide Oxidation and/or hydroxidation of the surface of Cu spices were proved to be a feasible process to moderate CRR performance of Cu-based electrocatalysts. [112] For instance, Broekmann et al revealed that the coexistence of Cu and Cu oxide on the activated Cu mesh could alter CRR mechanism and avoid the accumulation of poisoning surface species; consequently, it led to FE of 13% for C 2 H 5 OH and FE of 11.8% for n-PrOH (Figure 10a). [113] It was also reported by Hwang et al that the presence of Cu(OH) 2 on the surface of Cu electrode could effectively regulate the electrochemical reduction environment in CRR, which was critical in the formation of C 2 H 4 as CRR product.…”
Section: Cu Single Atomsmentioning
confidence: 99%